The false choices of rural development - Drachoussoff, V. (Technical Centre for Agricultural and Rural Cooperation, 1986)
We have received many letters from readers about the article by Mr. Drachoussoff which appeared in the pilot issue of ''SPORE''. For space reasons, we were obliged to make cuts in the text. Because of the positive response to this artic/e, we are...